Answer:
k = -5
g = 6
Explanation
1) First solve for k and plug that into the other equation to solve for g.
5g + 4k = 10
4k = -5g + 10
k = -5/4g + 2.5
2) Plug k into the other equation to solve for g
-3g - 5k = 7
-3g = 5k + 7
-3g = 5(-5/4g + 2.5) + 7 Use the distributive property
-3g = -6.25g + 12.5 + 7 Combine like terms and simplify
-3g = -6.25g + 19.5 Add 6.25g to both sides
3.25g = 19.5 Divide 3.25 from both sides to find g
g = 6
3) Now we take this g and plug it into the other equation to find k
(we could also just plug it into this equation as well)
5g + 4k = 10
5(6) + 4k = 10
30 + 4k = 10
4k = -20
k = -5.
If we really wanted to doube check this then we could plug the k value into the equation we used to find the g value...
-3(6) - 5(-5) = 7
-18 + 25 = 7
So yes, k = -5 and g = 6.